Multiple Locus Variable-Number Tandem-Repeat and Single-Nucleotide Polymorphism-Based Brucella Typing Reveals Multiple Lineages in Brucella melitensis Currently Endemic in China - Sun, Mingjun; Jing, Zhigang; Di, Dongdong; Yan, Hao; Zhang, Zhicheng; Xu, Quangang; Zhang, Xiyue; Wang, Xun; Ni, Bo; Sun, Xiangxiang; Yan, Chengxu; Yang, Zhen; et al. (Frontiers in Veterinary Science, 2017)
Brucellosis is a worldwide zoonotic disease caused by Brucella spp. In China, brucellosis is recognized as a re-emerging disease mainly caused by Brucella melitensis specie. To better understand the currently endemic B. melitensis strains in China, three Brucella genotyping methods were applied to 110 B. melitensis strains obtained in past several years. By MLVA genotyping, five MLVA-8 genotypes were identified, among which genotypes 42 (1-5-3-13-2-2-3-2) was recognized as the predominant genotype, while genotype 63 (1-5-3-13-2-3-3-2) and a novel genotype of 1-5-3-13-2-4-3-2 were second frequently observed. MLVA-16 discerned a total of 57 MLVA-16 genotypes among these Brucella strains, with 41 genotypes being firstly detected and the other 16 genotypes being previously reported. By BruMLSA21 typing, six sequence types (STs) were identified, among them ST8 is the most frequently seen in China while the other five STs were firstly detected and designated as ST137, ST138, ST139, ST140 and ST141 by international MLST database. WGS-SNP based typing and phylogenetic analysis resolved Chinese B. melitensis strains into five clusters, reflecting the existence of multiple lineages among these Chinese B. melitensis strains. In phylogeny, Chinese lineages are more closely related to strains collected from East Mediterranean and Middle East countries, such as Turkey, Kuwait and Iraq. In next few years, MLVA typing will certainly remain an important epidemiological tool for Brucella infection analysis, as it displays a high discriminatory ability and achieves result largely in agreement with WGS-SNP based typing. However, WGS-SNP based typing is found to be the most powerful and reliable method in discerning Brucella strains and will be popular used in the future.